Progress of deep brain stimulation for Parkinson's disease - BAI Yu⁃tong; YANG An⁃chao; ZHANG Jian⁃guo (Chinese Journal of Contemporary Neurology and Neurosurgery)
As a mature neuromodulation technique, deep brain stimulation (DBS) has been widely used in the treatment of various neurological and psychiatric disorders. Parkinson's disease (PD) is one of the earliest indications for DBS and has received the most treatment so far. It has attracted extensive attention and in⁃depth research from the academic community for a long time, and has made remarkable progress in multiple fields. This review highlights the optimization of DBS for PD, focusing on two key directions: surgical technology innovation and neural circuit mechanism research. It explores the surgical technology innovation, equipment innovation, and programming strategy improvement of DBS, as well as the recognition and application of neural circuit markers. These studies not only significantly improve the efficacy of PD treatment, but also provide valuable ideas and scientific basis for the future development of neuromodulation technique.